General Self-Confidence and Its Implication On Students’ Achievement In Oral Presentation - Salim, Agus (JEELS (Journal of English Education and Linguistics Studies), 2015)
In speaking course, the teachers usually ask the students to present their projects in front of the class through an activity called Oral Presentation. However, many of students are afraid of public speaking due to the effect of self-confidence. This study is aimed to (1) describe general self-confidence among Indonesian EFL learners, (2) describe their academic achievement in oral presentation, and (3) find out the relationship between self-confidence and their academic achievement in oral presentation. Correlational design is used to investigate the existence or non existence of the relationship between the variables. The subjects of this study are 68 students at the second semester in English Department of one private university in Lamongan, Indonesia. Documentation and questionnaire are used as instruments to collect the data in this study. The findings reveal that (1) the students‘ general selfconfidence is quite strong, (2) the students‘ academic achievement in the oral presentation is good, and (3) the two variables show high correlation. Therefore, the teachers are suggested to enforce activities that could increase students‘ self-confidence which in turn could decrease their anxiety in public speaking.